Antibodies against Anthrax: Mechanisms of Action and Clinical Applications - Thibaut Pelat; Philippe Thullier; Jeffrey W. Froude II (Toxins, 2011)
B. anthracis is a bioweapon of primary importance and its pathogenicity depends on its lethal and edema toxins, which belong to the A-B model of bacterial toxins, and on its capsule. These toxins are secreted early in the course of the anthrax disease and for this reason antibiotics must be administered early, in addition to other limitations. Antibodies (Abs) may however neutralize those toxins and target this capsule to improve anthrax treatment, and many Abs have been developed in that perspective. These Abs act at various steps of the cell intoxication and their mechanisms of action are detailed in the present review, presented in correlation with structural and functional data. The potential for clinical application is discussed for Abs targeting each step of entry, with four of these molecules already advancing to clinical trials. Paradoxically, certain Abs may also enhance the lethal toxin activity and this aspect will also be presented. The unique paradigm of Abs neutralizing anthrax toxins thus exemplifies how they may act to neutralize A-B toxins and, more generally, be active against infectious diseases.